Motivasi Mahasiswa Memilih Jurusan Pendidikan Luar Biasa (PLB) - Bhennita Sukmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study, to determine the motivation of students choosing the PLB majors, so that the factors behind the motivation obtained, including intrinsic factors related to desires or desires and ideals in themselves and extrinsic factors which are factors of support for parents and friends . The research method uses qualitative descriptive methods that aim to reveal actual field data regarding the current objective conditions. The results of the study showed that the motivation of students to choose the PLB department was 28% because of intrinsic factors related to the desire or desire to become a PLB teacher and 27% chose because of the aspirations so that many students were very enthusiastic in learning and understanding ABK lessons. In addition, in extrinsic factors as many as 24% chose the PLB department because of the support of parents and accepting parental advice and 21% of students chose the PLB department because of the encouragement of friends whose friends chose the PLB major. Conclusion, more intrinsic factors are taken into consideration in choosing PLB majors than extrinsic factors. Keywords: Motivation, Extraordinary Education (PLB), Students